Yathong Trough deep 2D reflection seismic survey - identifying major structures for the southern Cobar Basin, NSW. Issue 1 (1st December 2016) - Hegarty, Rosemary; Carlton, Astrid; Czarnota, Karol
Abstract : Two 2D deep seismic reflection survey lines totalling 229 km in length were completed in western NSW by the Geological Survey of New South Wales (GSNSW) under the New Frontiers initiative. Contract management for seismic acquisition and data processing were conducted by Geoscience Australia (GA), with funding for data processing contributed by Coal Innovation, NSW Industry. The survey aimed to detail the stratigraphy of thick Devonian sequences within the Yathong Trough in the eastern Darling Basin. Survey line YT2 was extended eastwards across the southern Cobar Basin over rift-phase volcanic sequences of the Cobar Supergroup in the Mount Hope and Rast Troughs. The objective of acquiring 20 s two-way time data was to identify major structural elements, crustal architecture, and to improve understanding of this mineralised region. Preliminary interpretation of the deep 2D seismic data by GSNSW and GA has recognised reflector domains and discontinuities below the surface outcrops (in the east) and also within basement rocks beneath the basin sequences. These were considered in the context of regional aeromagnetic and gravity data, and previous deep seismic profile interpretations for the Cobar region. The key results are definition of crustal thickness and interpretation of prominent fault structures in the upper and middle crust. In particular, good correlation was found between near-surface fault zones (from geological mapping or interpreted from potential field data) and faulting related to a major west-dipping high-angle seismic discontinuity that penetrates to the middle levels of the lower crust. This presentation describes the interpretation of major reflective horizons and structures, identifying upper, middle and lower crustal features. The profiles and interpretations will provide valuable input for regional geodynamic studies. Increased structural understanding may assist the search for additional gold and copper deposits in the southern Cobar Basin.